PENGEMBANGAN PARIWISATA SUMATERA BARAT - Syafnidar, Syafnidar (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2007)
In the autonomy era, each of local government has program to take break through action to increase the source of development budget. It mean that local government required to find new strategy to increase their development budget. The initiative to find new strategy is very important especially to the province who does'n have sufficient natural resourch such as Sumatera Barat, bengkulu and other province. Sumatera Barat has a great potensial in tourism sector, it has advantages in naturaly esthetic, interisting culture and custom, and specific market segment particularly tourist of Minang Kabau people wich spread out all over Indonesia and ethnic family of Negeri Sembilan. The goals of developing tourism sector are: (1) Improve economic viability of tourism, (2) Advance local support of tourism, (3) Increasecooperation emong all section, and (4) Enhance promotional and marketing.